Prognostic Implications of a Second Peak of High-Sensitivity Troponin T After Myocardial Infarction - Hartikainen, Tau S.; Goßling, Alina; Sörensen, Nils A.; Lehmacher, Jonas; Neumann, Johannes T.; Blankenberg, Stefan; Westermann, Dirk (Frontiers in Cardiovascular Medicine, 2022)
Background: After an acute myocardial infarction (MI), repeated measurement of cardiac biomarkers is commonly performed, although not recommended in current guidelines. There is only limited data on the kinetics of troponin in this phase. For high-sensitivity cardiac troponin T (hs-cTnT), but not high-sensitivity cardiac troponin I (hs-cTnI), late increases in terms of a second peak have been described. Their impact on the prognosis of patients with MI remains unclear. Methods: We included 2305 patients presenting to the emergency department with symptoms suggestive of MI. 507 were diagnosed with MI. Hs-cTnT, creatine kinase (CK) and the MB fraction of CK (CK-MB) were measured at admission, after 1 and 3 hours and thereafter as indicated by the treating physician. A mixed-model approach was applied for modelling the biomarker kinetics. All patients were followed up to assess a composite endpoint of mortality, recurrent MI, revascularization and rehospitalization and to investigate the effect of a second hs-cTnT peak on prognosis. Results: Out of 507 patients with MI, 192 had a sufficient amount of hs-cTnT measurements after the index MI. In 111 (57.8%) patients a second hs-cTnT peak was found after 4.48 days. For CK and CK-MB a second peak could not be identified. Regarding the composite endpoint there was no significant difference between patients with and without a second hs-cTnT peak. Conclusion: In our analyses, a second peak of hs-cTnT after an acute MI was common, but not associated with poorer outcome. Thus, the clinical value of hs-cTnT for monitoring myocardial ischemia might be limited in this phase and other biomarkers might be more suitable.